Pengelolaan Arsip Elektronik Sistem Surat Masuk Dan Surat Keluar Di Kantor Kementerian Hukum Dan Hak Asasi Manusia Sulawesi Selatan - Pratiwi, Rizky Amalia; Madani, Muhlis; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2023)
This study purposed to find out the Electronic Archive Management of the Incoming and Outgoing Mail System at the Regional Office of the Ministry of Law and Human Rights of South Sulawesi during the implementation of the online incoming and outgoing mail system application. This study used descriptive qualitative research. Data collection techniques were observation, interviews and documentation. The results of this study showed that from the aspects of 1) the creation and storage of managing electronic archives had been integrated into the SISUMEKER Incoming and Outgoing Mail System application at the Regional Office of the Ministry of Law and Human Rights of South Sulawesi, 2) distribution and use, in the management of electronic archives. implementing the incoming and outgoing mail system application as the way in which the use of the application could be easier for employees, 3) maintenance in the SISUMEKER Electronic Archive Management was carried out properly. It was known from the ability to maintain in accordance with the plan. It maintained the quality of the management each account SISUMAKER. Also the employees routinely did backup data so that archives were kept safe, 4) disposition of the SISUMAKER Incoming and Outgoing System Electronic Archive Management had been carried out in stages and it run through the sisumaker application.